2009
DOI: 10.1002/ijc.24938
|View full text |Cite
|
Sign up to set email alerts
|

The Arf‐inducing transcription factor Dmp1 encodes a transcriptional activator of amphiregulin, thrombospondin‐1, JunB and Egr1

Abstract: Dmp1 (Dmtf1) encodes a Myb‐like transcription factor implicated in tumor suppression through direct activation of the Arf‐p53 pathway. The human DMP1 gene is frequently deleted in non‐small cell lung cancers, especially those that retain wild‐type INK4a/ARF and/or p53. To identify novel genes that are regulated by Dmp1, transcriptional profiles of lung tissue from Dmp1‐null and wild‐type mice were generated using the GeneChip Microarray. Comparative analysis of gene expression changes between the two groups re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…41,42 A recent study implicated JunB as one of the targets of Dmtf1, showing that its expression was decreased in lung cells from Dmtf1-KO mice. 43 We therefore predicted reduced JunB expression in sorted KSL cells, B cells, and CD4 T cells from KO mice relative to similar WT cells ( Figure 6) and increased B-cell populations with reciprocal T-cell reductions in both primary KO mice and mice transplanted with KO BM cells (Table 1 and supplemental Figure 2). These findings are consistent with previous observations about distinctive JunB function in T and B cells, suggesting that JunB is potentially involved in a Dmtf1-mediated, Arf-independent pathway.…”
Section: Regulation Of Stem-cell Quiescence Bymentioning
confidence: 89%
“…41,42 A recent study implicated JunB as one of the targets of Dmtf1, showing that its expression was decreased in lung cells from Dmtf1-KO mice. 43 We therefore predicted reduced JunB expression in sorted KSL cells, B cells, and CD4 T cells from KO mice relative to similar WT cells ( Figure 6) and increased B-cell populations with reciprocal T-cell reductions in both primary KO mice and mice transplanted with KO BM cells (Table 1 and supplemental Figure 2). These findings are consistent with previous observations about distinctive JunB function in T and B cells, suggesting that JunB is potentially involved in a Dmtf1-mediated, Arf-independent pathway.…”
Section: Regulation Of Stem-cell Quiescence Bymentioning
confidence: 89%
“…Data from ChiP (99), Chip on Chip (169), and Chip-Seq (170) revealed that ~50% of promoters occupied by mtp53 contained ETS-binding sites, suggesting that physical binding with ETS proteins is an essential mechanism by which mtp53 regulates gene expression for oncogenic transformation (159, 160). Importantly, these mtp53-bound genomic regions do not have a WTp53 response element 5′-PuPuPuC(A/T)(A/T)GPyPyPy-3 (171), indicating that the mtp53 proteins do not cause transformation through direct binding to DNA (159).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…In fact, for example, a study using Dmp1 C/C , Dmp1 C/¡ , and Dmp1 ¡/¡ mice showed such results for the transcription factor Dmp1 (Dmtf1). 21 The on-off switchlike response via NDs may also be relevant to a sharp spatial boundary of expression in response to the gradient of the transcription factor Bicoid, a morphogen in Drosophila development. 7 In the switch model, as long as a transition between the "on" and "off" phases is involved, even a relatively moderate up or downregulation of a transcription factor may result in drastic changes in expression levels of its target genes.…”
Section: Switch-like Response Via Natural Decoysmentioning
confidence: 99%